Climate, Soil Management, and Cultivar Affect Fusarium Head Blight Incidence and Deoxynivalenol Accumulation in Durum Wheat of Southern Italy - Scala, Valeria; Aureli, Gabriella; Cesarano, Gaspare; Incerti, Guido; Fanelli, Corrado; Scala, Felice; Reverberi, Massimo; Bonanomi, Giuliano (Frontiers in Microbiology, 2016)
Fusarium head blight is a multifaceted disease caused by some species of Fusarium spp. A huge production of mycotoxins, mostly trichothecenes, often accompanied this disease. Amongst these toxic compounds, deoxynivalenol (DON) and its derivatives represent a major issue for human as well as for animal health and farming. Common and durum wheat are amongst the hosts of trichothecene-producing Fusaria. Differences in susceptibility to fungal infection and toxin accumulation occur in wheat cultivars. Recently, increasing incidence and severity of Fusarium infection and a higher DON accumulation in durum wheat were observed in Italy, especially in Northern regions. In this study, we analysed wheat yield, technological parameters, the incidence of Fusarium infection and DON content in kernel samples of durum wheat coming from three locations of Southern Italy with different climatic conditions and grown during two seasons, with two methods of cultivation. Four different durum wheat cultivars prevalently cultivated in Southern Italian areas were chosen for this study. Our analysis showed the effects of environment and cultivar types on wheat productivity and key technological parameters for the quality level of the end-product, namely pasta. Notably, although a low rate of mycotoxin contamination in all study sites was assessed, an inverse relation emerged between fungal infection/DON production and durum wheat yield. Further, our study pinpoints the importance of environment conditions on several quality traits of durum wheat grown under Mediterranean climate. The environmental conditions at local level (microscale) and soil management practices may drive Fusarium head blight outbreak and mycotoxin contamination even in growing area suitable for cropping this wheat specie.